Leptomeningeal metastases in a case of squamous cell carcinoma of the uterine cervix : A case report along with review of literature - Datta, Anupam; Majumdar, Soumita; Dutta, Amitava; Sen, Partha (Indian Journal of Case Reports, 2025)
Leptomeningeal metastases (LM) is an extremely rare complication in solid malignancies and an indicator of poor prognosis. Our case is of a 54-year-old lady who was diagnosed with squamous cell carcinoma of the uterine cervix (FIGO Stage IVA). She received 6 cycles of systemic chemotherapy with paclitaxel, carboplatin, and bevacizumab and showed near complete metabolic response in the post 6th cycle response evaluation PET CT scan. After 3 more cycles of maintenance bevacizumab, she developed disease progression. She further developed drowsiness and disorientation. Gadolinium-enhanced MRI and cerebrospinal fluid cytology confirmed the presence of LM. She was treated with craniospinal irradiation along with pembrolizumab. To date, 28 cases of LM in cervical cancer have been reported worldwide, and here we report the 29th case. There is no established treatment protocol for LM yet, and an individualized multimodality approach is commonly used based on retrospective data and patient-specific characteristics.